A Multisystemic Pictorial Review of Diabetes Mellitus. (15th January 2021) - Shah, Tejen; Farooq, Zerwa; Cohen-Addad, Dan; DeAlwis, Delan
Abstract : Diabetes mellitus is a leading cause of death with immense burden on the health care system. The number of patients suffering from diabetes is expected to rise dramatically in the coming years secondary to lifestyle changes. Diabetes is a multisystemic disease that exerts its effects through decreased insulin sensitivity leading to various degrees of metabolic dysregulation. The pathogenesis of complications associated with diabetes is largely dependent on the duration of the disease and common coexisting conditions such as hyperlipidemia, hypertension, and obesity. Acute hyperglycemic and hypoglycemic events can lead to life-threatening illness such as acute coronary syndrome, hyperosmolar state, and diabetic ketoacidosis. The deleterious effects of long-standing diabetes are usually mediated by microvascular disease leading to diabetic retinopathy, nephropathy, cardiomyopathy, and neuropathy. Abstract : Supplemental Digital Content is Available in the Text.